(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The purpose of the present study was to examine the effectiveness of 12-week Greek traditional dances training for improving postmenopausal women cardiorespiratory fitness. Twenty three postmenopausal women, aged 55-68 years, were, randomly, chosen and separated to an experimental group (n=13) that attended a 12-week Greek traditional dances program at a frequency of three sessions per week, 50 minutes each, and a control group (n=10) that continued their daily habits for the same period. Cardiorespiratory fitness was assessed by the six-minute walking test (6MWT) and resting heart rate (HR). For data analysis, the non-parametric test Wilcoxon and Mann-Whitney U test, and Pearson correlation of the SPSS ver. 20.0 for windows was used. No significant difference in the baseline measures was detected between the two groups. After the intervention program it was found out a significant decrease in resting HR (z=-2.50, p<0.05) for the experimental group, but an increase for the control group. A significant increase in distance travelled during the 6MWT (z=-3.18, p<0.01) was observed in the experimental group, while the control group presented a significant decrease (z=-2.49, p<0.05). The results provide evidence for the effectiveness of Greek traditional dances programs in improving the cardiorespiratory fitness of postmenopausal women.